Synthesis of Asymmetrical Monobenzo‐Substituted Cobalt Thioporphyrazines and Their Biomimetic Catalytic Property. Issue 10 (17th October 2016) - Zhou, Peng; Jin, Juanjuan; Zhang, Bingguang; Yang, Changjun; Zhang, Zehui; Li, Zhe; Deng, Kejian
Abstract: Two novel monobenzo porphyrazines bearing nitro and methoxyl respectively on fused benzene ring were successfully synthesized. Also, an asymmetrical porphyrazine with one butylthio branch at the pyrrolic β ‐position substituted by hydrogen atom was successfully isolated in the course of synthesis of symmetric octakis(butylthio) porphyrazine. Their corresponding cobalt complexes were subsequently obtained and characterized. Their catalytic ability was assessed by aerobic oxidation of benzoin, showing the highest benzil yield of 95.2% for 60 min. A possible mechanism was also presented from the in‐situ UV‐Vis spectra, in which a novel and characteristic absorption peak of metal‐oxo was observed. At the same time, similar results of the extended oxidation of benzyl alcohol also confirmed the reactive mechanism. Abstract : Two novel monobenzoporhyrazines bearing nitro and methoxyl respectively on fused benzene ring were successfully synthesized. The catalytic ability of their corresponding cobalt complexes was assessed by aerobic oxidation of benzoin to benzil.